Subcutaneous Panniculitis-like T-Cell Lymphoma with a Transformation to Lupus Erythematosus Panniculitis: A Case Report - Weeratian Tawanwongsri; Jirapan Thongsroy (Case Reports in Dermatology, 2022)
Subcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare primary cutaneous lymphoma characterized by infiltration of the subcutaneous tissue by neoplastic cytotoxic T cells mimicking panniculitis. There is a strong association between SPTCL and lupus erythematosus panniculitis (LEP). However, patients who were diagnosed with LEP with a preceding diagnosis of SPTCL have been scarcely reported. We herein reported a 21-year-old Thai woman presenting to a dermatology clinic for evaluation of a 1-month history of a painful mass on the right buttock and bilateral upper eyelid swelling. A subcutaneous mass which was 5 by 2 cm in diameter, tender, firm, and fixed with a smooth surface was palpated over the upper outer quadrant of her right gluteal area. After a diagnosis of SPTCL had been made based on the histological and immunohistochemical studies, treatment with oral dexamethasone and ciclosporin A was initially started. Because of intolerance to adverse reactions of dexamethasone, only ciclosporin A was given. Improvement was not achieved at 6-month follow-up. She then underwent the re-incisional biopsy at the same gluteal area and the histological features were consistent with LEP. After hydroxychloroquine was given, the lesion resolved within 3 months, and no recurrence was detected during the following 6-month follow-up. We emphasize that long-term follow-up of patients with SPTCL is required. Additionally, in case of poor response to the given treatment, a repeat skin biopsy should be considered in order to determine the proper management.